Interrogating key determinants of poverty and inequality in South Africa since 1994 using life circumstances and service delivery indicators - Masiteng, Kefiloe Doris (My University, 2016)
The study articulates the key indicators that are drivers of poverty and inequality in the post-apartheid society. Historically, education, employment, household income and service delivery were not used as the foundation for measuring poverty and inequality in the country. Specific objectives for this study are to interrogate the key determinants that have influenced poverty and inequality in South Africa since 1994, and to investigate how the predictors of life circumstances and service delivery changed across the population over the period 1994–2007. Descriptive analysis was used on household surveys (General Household Survey (GHS) 2002–2011, Quarterly Labour Force Survey (QLFS) 2008–2011 and Living Conditions Survey (LCS) 2008 and 2011) to determine changes and trends in the living conditions of the population. Multivariate analytical approaches were applied on CS 2007 data with a sample of 360 000 households conducted by Statistics South Africa. Statistical regression models were developed for life circumstances and service delivery measures to explain poverty and inequality. Principal component analysis was applied on CS 2007 to promote multidimensional approaches for poverty and inequality measurement using development indicators as the components for life circumstances and service delivery. The main findings of the study show that low levels of education and high unemployment are the determinants of poverty and inequality. Positive linear relationships between educational attainment and age, employment and population group, age, sex and educational level of household head were established. Income disparities further perpetuate disparities in life circumstances and service delivery. Disparities service delivery are not the determinants but the consequences of poverty and inequality. Poverty and inequality in South Africa are structural showing that, while many people progressed in the last twenty-two years, many remained behind, and even progressed negatively as they remained worse off based on data since the 1996 census. While much work has been conducted on life circumstances such as education, employment and income, work on service delivery in relation to poverty is still limited and thus deserves more attention
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2016.
Keywords: Poverty--South Africa; Income distribution--South Africa; Unemployment--South Africa; Poor--Education--South Africa